THE OBSERVATIONS OF ARTIFICIAL SATELLITES AND SPACE DEBRIS USING KT-50 TELESCOPE IN THE ODESSA UNIVERSITY - Shakun, L.; Korobeynikova, E.; Koshkin, N.; Melikyants, S.; Strakhova, S.; Terpan, S.; Burlak, N.; Golubovskaya, T.; Dragomiretsky, V.; Ryabov, A. (Одеські астрономічні публікації, 2016)
In paper the equipment, images analysis techniques in the frame and the method of the satellite brightness estimation in the standard photometric system are describes. Within two years, on the KT-50 telescope were obtained measurements of about two hundred objects in more than 2,000 passages. The results of statistical analysis of actual data observations array in 2015 and 2016 are given.